Analisis Karakter, Kerja Sama Dan Kompetensi Guru/Fasilitator Sekolah Alam Ar Ruhama Pekanbaru - Yusriadi, Yusriadi (Eko dan Bisnis: Riau Economic and Business Review, 2023)
This study aims to provide an overview of the Analysis of Character, Collaboration, and Competence of Teachers/Facilitators at Ar Ruhama Natural School in Pekanbaru City. The research method employed a quantitative approach with a descriptive design. Data collection was conducted using questionnaires, and data analysis was performed using descriptive analysis in the form of frequency tables. The findings of this study indicate that the teachers/facilitators at Ar Ruhama Natural School in Pekanbaru demonstrate good daily behavioral characteristics, exhibit proficient collaboration skills, and possess a high level of competence.